Antioxidative Properties and Ability of Phenolic Compounds of Myrtus communis Leaves to Counteract In Vitro LDL and Phospholipid Aqueous Dispersion Oxidation. Issue 7 (24th June 2014) - Dairi, Sofiane; Madani, Khodir; Aoun, Manar; Him, Joséphine Lai Kee; Bron, Patrick; Lauret, Céline; Cristol, Jean‐Paul; Carbonneau, Marie‐Annette
Abstract Antioxidant activities of Myrtus communis leaf phenolic compounds (McPCs) were investigated on 2, 2′‐9‐azino‐bis‐3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS+) and oxygen radical absorbance capacity (ORAC) tests or on oxidation of biological models, human low‐density lipoprotein (LDL) and phospholipid aqueous dispersion (l‐α‐phosphatidylcholine stabilized by bile salts). Two extraction techniques, microwave‐assisted (MAE) and conventional (CE), were used to isolate McPCs, producing similar results of phenolic compound content. ABTS+ assay showed clearly that myrtle extracts exhibited a stronger scavenging effect than butylated hydroxyanisole and α‐tocopherol, with a slight advantage for myrtle CE extract. In ORAC assay, the both McPC extracts were similarly less effective than the pure compounds as caffeic acid and myricitrin (myricetin 3‐O‐rhamnoside) but stronger than butylated hydroxytoluene. Moreover, myrtle CE and MAE extracts, and myricitrin were able to inhibit similarly the production of conjugated dienes and to prolong the lag phase (Tlag) during Cu2+‐induced LDL oxidation with a dose‐response effect. The cryo‐electron microscopy observations on studied phospholipid dispersion stabilized by bile salts (BS) revealed the presence of bilayer vesicles and micelles. In 2, 2′‐azobis (2‐amidinopropane) hydrochloride–induced phospholipid/BS oxidation, myrtle CE and MAE extracts gave similar effects to α‐tocopherol and caffeic acid but myricitrin showed a higher protective effect than myrtle extracts. We showed also that no synergic or additive effect between α‐tocopherol and myrtle extracts or caffeic acid in α‐tocopherol–enriched phospholipid/BS dispersion, but myricitrin showed an additive effect and thus promoted the total antioxidant activity. These data showed that myrtle extract could be used as potential natural antioxidants, food stabilizers, or natural health products.